Key Role of Human ABC Transporter ABCG2 in Photodynamic Therapy and Photodynamic Diagnosis - Toshihisa Ishikawa; Hiroshi Nakagawa; Yuichiro Hagiya; Naosuke Nonoguchi; Shin-ichi Miyatake; Toshihiko Kuroiwa (Hindawi Limited, 2010)
Accumulating evidence indicates that ATP-binding cassette (ABC) transporter ABCG2 plays a key role in regulating the cellular accumulation of porphyrin derivatives in cancer cells and thereby affects the efficacy of photodynamic therapy and photodynamic diagnosis. The activity of porphyrin efflux can be affected by genetic polymorphisms in the ABCG2 gene. On the other hand, Nrf2, an NF-E2-related transcription factor, has been shown to be involved in oxidative stress-mediated induction of the ABCG2 gene. Since patients have demonstrated individual differences in their response to photodynamic therapy, transcriptional activation and/or genetic polymorphisms of the ABCG2 gene in cancer cells may affect patients' responses to photodynamic therapy. Protein kinase inhibitors, including imatinib mesylate and gefitinib, are suggested to potentially enhance the efficacy of photodynamic therapy by blocking ABCG2-mediated porphyrin efflux from cancer cells. This review article provides an overview on the role of human ABC transporter ABCG2 in photodynamic therapy and photodynamic diagnosis.